2015
DOI: 10.1039/c5ra10581a
|View full text |Cite
|
Sign up to set email alerts
|

Methanol formation by catalytic hydrogenation of CO2on a nitrogen doped zinc oxide surface: an evaluative study on the mechanistic pathway by density functional theory

Abstract: An investigation of the nature of adsorption of H 2 O and CO 2 on a nitrogen doped zinc oxide cluster surface and the resultant reaction between them has been performed using hybrid density functional theory (DFT) calculations at the B3LYP level of theory in a vacuum. The stable chemisorption modes of CO 2 and H 2 O on metal, oxygen and nitrogen sites were examined. The calculated adsorption energies reveal that the formation of CO 2 À attached to N is the most favorable process for CO 2 on the Zn 18 O 17 :N c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…The desorption/formation energy 52,53 of the product methanol (CH 3 OH) is calculated to be À2.23 eV, which is more negative than that of the previously reported studies, 54 thus indicating an exothermic reaction and the superiority of the ZnO nanocage for methanol production.…”
Section: Geometrical Analysis Of Pristine and Ag-decorated Zno Nanocagesmentioning
confidence: 60%
“…The desorption/formation energy 52,53 of the product methanol (CH 3 OH) is calculated to be À2.23 eV, which is more negative than that of the previously reported studies, 54 thus indicating an exothermic reaction and the superiority of the ZnO nanocage for methanol production.…”
Section: Geometrical Analysis Of Pristine and Ag-decorated Zno Nanocagesmentioning
confidence: 60%
“…16,32 The peak corresponding to the adsorbed surface hydroxyl has been more pronounced for the IZO 50 film compared to the IZON films, which is attributed to reduced adsorption of water molecules on the nitrogen doped metal oxides. 33,34 The ratios of areas under curves A V /A L (A V and A L are the area under the curve for non-stoichiometric and lattice oxygen, respectively) for IZON 25, IZON 50, IZON 75 and IZO 50 have been estimated to be 1.12, 1.17, 1.08 and 0.85 respectively. The increase in oxygen vacancy (related to non-stoichiometric oxygen) in the IZON films has been accredited to doping.…”
Section: Chemical Characterizationmentioning
confidence: 99%
“…Further theoretical studies have confirmed the preferential adsorption of oxygen compared to water molecules in nitrogen doped metal oxides, which also reduces the influence of water molecules on the sensing performance of nitrogen doped metal oxide under high humid conditions. 34,41 The ethanol sensing response of IZON 50 has been examined over an extended period. As shown in Fig.…”
Section: Gas Sensing Propertiesmentioning
confidence: 99%
“…The CO 2 catalytic fixation process on different surfaces was studied by Tang et al, and the binding strength is the inverse of the stability of the chosen surface . Not only that, the (101̅0) or (0001) surface can be an effective medium for urea adsorption and decomposition, methanol reaction or other organic reaction, and small-molecule adsorption. , More than the specified crystal indices, the metal oxide nanoparticles were also used to evaluate the gas-sensing properties. By doping N atom on the surface, the cohesive energy between the O 3 /NO 2 molecule and the ZnO nanoparticle can be significantly increased .…”
Section: Introductionmentioning
confidence: 99%